Neem Oil (Azadirachta indica L.) Response Surface Methodology (RSM)-Optimized Nanoemulsions for Sensory Quality Preservation of Oreochromis niloticus Fillets - Jamal Kazam; Khalid Javed Iqbal; Afshan Shafi; Usman Majeed; Maximilian Lackner (Biology)
Neem oil nanoemulsions (NO NEs) have gained attention as natural antibacterial agents due to toxicity concerns surrounding synthetic preservatives. This study aimed to prepare a response surface methodology (RSM)-optimized NO NE < 200 nm to achieve a stable dip solution to maintain the sensory quality of Oreochromis niloticus fillets. The NO NE achieved a stable formulation with a particle size of 160.2 ± 0.04 nm on average. The polydispersity index (PDI) was 0.1 ± 0.05, and the zeta potential was found to be 18.2 ± 0.09 mV. Gas chromatography confirmed the presence of nimbiol, nimbandiol, 6-deacetyl nimbinene, and azadirachtin in NO after ultrasonic homogenization for 10 min (alternating between 30 s rest and 30 s work time). The NE had a spherical shape with a smooth surface, as was evident from transmission electron microscopy (TEM). Furthermore, NO:PM (neem oil–potassium metabisulphite) had an MIC (minimum inhibitory concentration) value of 150 ppm, compared to 210 ppm for the NO NE alone, against Staphylococcus aureus. Time–kill dynamics revealed the more effective control of S. aureus until 72 h with NO:PM. Moreover, DNA and protein leakage also increased from 0.145 ± 0.001 to 0.769 ± 0.002 OD (optical density) and from 0.142 ± 0.002 to 0.740 ± 0.001 OD, respectively, with the co-formulation of NO:PM. Conclusively, NO:PM inhibited S. aureus at a lower dose compared to the NO NE alone. Time–kill dynamics revealed complete inhibition of S. aureus in vitro for a period of 72 h. On the other hand, a proximate analysis of O. niloticus fillets showed no alteration in pH, no protein loss, and juiciness/moisture retention during 30 days of storage (4 °C). Sensory panelists reported that O. niloticus fillets treated with NE NO had improved color, flavor, juiciness, aroma, and overall quality. These results show that NE NO is a suitable green preservative for fish and possibly other meat-based products.